Islam and secular citizenship in the Netherlands, United Kingdom, and France - Ivanescu, Carolina (Religion and global migrations, 2016)
The imaginery -- Secularization, secularity, and the secular: religion and its place in social life -- The symbolic -- Nation, citizenship, and religious migrants -- The real -- Rotterdam, politicized religion -- Leicester, civic religion -- Marseille, symbolic religion -- Comparing regimes of secularity, citizenships and fields of Muslimness -- Concluding reflections